Successful Trial of Labor After Two Caesarean Sections (TOLA2C): Analysis of a Delivery Protocol with Feto-Maternal Outcome - Brandstetter, Maximilian; Brandstetter, Andreas; Kainz-Schultes, Sabine; Jacobs, Volker R.; Fazelnia, Claudius; Fischer, Thorsten; Bogner, Gerhard (Geburtshilfe und Frauenheilkunde, 2025)
The majority of obstetrical clinics do not offer a trial of labor after two Caesarean sections (TOLA2C) due to concerns about fetal and maternal complications such as uterine rupture or asphyxia. This study aimed to establish a delivery protocol for safely undergoing TOLA2C and analyzed predictors for a successful vaginal delivery.Analysis of retrospectively collected data of all pregnant women after two consecutive Caesarean sections was performed at the Obstetrics Department of a tertiary community hospital from January 2013 until December 2022. Those who desired TOLA2C were screened by a senior obstetrician and had to consent to a delivery protocol consisting of five pre- and eight peripartum criteria. Maternal demographic data, indications for previous Caesarean sections and feto-maternal outcome parameters were compared between the successful TOLA2C group and the intrapartum Third-Caesarean section group.In the study period, 385 women planned a delivery after two consecutive CS. Following the protocol, 358 patients (93.0%) were scheduled as elective repeat CS, while 27 (7.0%) attempted vaginal delivery. In this TOLA2C group, 17 women (63.0%) successfully delivered vaginally. In contrast, ten failed vaginal attempts (37.0%) resulted in nine intrapartum repeat CS and one intrapartum emergency CS. Women with prior vaginal delivery had a higher chance of a successful TOLA2C (p = 0.04). In comparison, women with a previous CS due to the indication of arrested labor had a higher risk for intrapartum repeat CS (p = 0.02). No fetal or maternal death occurred, and no major complications were observed.Under the specified conditions, TOLA2C is safe for mother and fetus, and successful vaginal delivery is feasible.
Keywords: Caesarean section; TOLA2C; feto-maternal morbidity; delivery mode